Improving Skills Speaking Commenting Materials on Issues Factual Discusion on Method and Photo Media Journalism Class V-B MIN Kertak Hanyar II Kabupaten Banjar - wati, Masra (Jurnal PTK dan Pendidikan, 2016)
This study aims to improve student learning outcomes VB class second semester at MIN gnashing Hanyar II to Indonesian lesson by using the method of discussion and media photojournalism on material factual comment on the issue. The method used in this research is descriptive qualitative method classroom action research study conducted in two cycles. The subjects were students of class VB MIN KertakHanyar II in the second semester of the school year 2014/2015, the number of 22 people. Collecting data in this study were obtained through observation, interview and test (writing). Data analysis technique used is the average and percentage. The results of the learning activities are: 1) Activities of teachers increased from 72.21% to 85.19%; 2) Participation of students has increased from 67.86% to 85.72%. The results consist of individual learning and classical: 1) the result of increased individual student mastery of 78.57% to 90.48% above the standard minimum mastery learning Indonesian subjects that have been established which is 70.00; 2) the results of students' increasing mastery of the classical also increased from 77.27% to 100% above the standard classical completeness 80%. From the above results, it can be said that the media use of photojournalism with discussion method can improve their speaking ability in subjects Indonesian VB class II MIN gnashing Hanyar Banjar district. Keywords: comment on the factual issues, the discussion method, media photojournalism